Human Factor in the Creation and Development of Energy Independent and Energy Efficient Rural Settlements - YASNOLOB, Ilona; CHAYKA, Tetyana; DIADYK, Tetiana; RUDYCH, Alla; BEZKROVNYI, Oleksandr; DANYLENKO, Viktoriia; SHULGA, Lyudmyla; SVITLYCHNA, Alla (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).10, 2019)
The author's approach as to the impact of human factor on the possibility to create and develop energy efficiency of villages, providing their energy independence of difficult situation with conventional energy sources in Ukraine has been suggested in the article. The calculation of human development index in the agrarian sector of the Ukrainian economy during 2010-2017 has been conducted which enabled to reveal the negative tendency as to decreasing the level of employees’ education. It has been determined that the human development index and the human development index of the Ukrainian economy’s agrarian sector are within the average level with the slight positive dynamics of growth. It has been emphasized that under these conditions receiving higher education is a priority task both for each employee and for agricultural enterprises, which must contribute to the improvement of their employees’ qualification level and training new professions. The model of the impact of educational level of employees in the agrarian sector of the economy on energy efficiency has been presented, taking into account the promising directions of energy independence and energy efficiency development of rural settlements.